Excellent teachers’ strategies in managing students’ misbehaviour in the classroom / Rosilawati Sueb ... [et al.] - Sueb, Rosilawati; Hashim, Hamimah; Hashim, Khadijah Said; Mohd Izam, Munirah (Universiti Teknologi MARA, 2020)
The study explores Excellent Teachers’ strategies in managing students’ misbehavior in the classroom. Students’ misbehavior are escalating and getting more variant and serious. The need to investigate how teachers manage the students’ behavior in the classroom is deemed important. In this study the participants are Excellent Teachers or “Guru Cemerlang” who earned their title as “Guru Cemerlang”, based on promotional basis, due to their expertise in their teaching areas, exhibition of exceptional qualities in their personality and leadership and accumulation of vast teaching experiences. This is a qualitative study utilized semi-structured interviews and email interviews as its data collection method. The interviews were conducted on nine (9) Malay Muslim Excellent Teachers; seven (7) females and two (2) males from nine different schools of nine different school districts in Selangor. Their age ranges from thirty seven (37) to fifty three (53) years with teaching experiences ranging from ten (10) to thirty one (31) years. The strategies that Excellent Teachers utilize could be categorized into three higher categories: the first category pertaining to the preparation and activities that excellent teachers carried out in the classroom, the second category is interaction, which is the communication and reaction of excellent teachers towards student misbehavior and the third category is the presentation of treatment pertaining to pleasant or unpleasant consequences. In this article only discussion on the first category of the strategy which pertain to preparation and activities that excellent teachers carried out in the classroom will be highlighted. The sub- strategies are recognized as early year preparation, conducive learning environment, and classroom activities.